2020
DOI: 10.4018/978-1-5225-9787-2.ch011
|View full text |Cite
|
Sign up to set email alerts
|

A Collaborative Framework for Medical Tourism Service Supply Chain Operations

Abstract: Medical tourism is a combination of medical and tourism services that attracts medical travelers to destination countries. Collaboration between the members of the medical tourism service supply chain (MTSSC) is important to maintain a sustainable business. Thus, in this chapter, the authors use Collaborative Planning Forecasting Replenishment (CPFR) model as a reference and adapt it for medical tourism services. The focus of this chapter is on the collaboration between an assistance company and a medical inst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 86 publications
0
2
0
Order By: Relevance
“…The full text of the 53 papers was read and forward and backward reference searches were conducted when other relevant articles were identified (Prataviera et al, 2020). Also, existing literature reviews on the topic of service supply chains were analyzed (Altuntas Vural, 2017; Choudhury et al, 2020; Karadayi‐Usta & SerdarAsan, 2014; Liu et al, 2017; Maas et al, 2014; Tokman & Beitelspacher, 2011; Wang et al, 2015). At the end of the structured search only two papers, Ellram et al (2004) and Baltacioglu et al (2007) were found to be significant attempts to develop cross‐functional, relationship‐based, service supply chain frameworks.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The full text of the 53 papers was read and forward and backward reference searches were conducted when other relevant articles were identified (Prataviera et al, 2020). Also, existing literature reviews on the topic of service supply chains were analyzed (Altuntas Vural, 2017; Choudhury et al, 2020; Karadayi‐Usta & SerdarAsan, 2014; Liu et al, 2017; Maas et al, 2014; Tokman & Beitelspacher, 2011; Wang et al, 2015). At the end of the structured search only two papers, Ellram et al (2004) and Baltacioglu et al (2007) were found to be significant attempts to develop cross‐functional, relationship‐based, service supply chain frameworks.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The current studies are mainly about the factors affecting medical tourism demand (Lin, Lee & Huang. 2009;Ferrer & Medhekar, 2012, Johnson & Garman, 2015Loh, 2015;Vetitnev, Kopyirin & Kiseleva, 2016;Tang & Lau, 2017;Tang & Abdullah, 2018;Loh & Triplett, 2019;Nilashi, Samad, Manaf, Ahmadi, Rashid, Munshi et al, 2019;Arulmozhi, Praveenkumar, Vinayagamoorthi, 2019;Al-Talabani, Kilic, Ozturen & Qasim, 2019;Sedianingsih, Ratnasari, Prasetyo & Hendarjatno, 2019), MTSSC management principles such as coordination, collaboration, information exchange and integration Perkumiene, Vienažindiene & Švagždiene, 2019;Cho & Lee, 2019;Karadayi-Usta & Serdarasan, 2019), perceived MTSSC quality (Debata, Patnaik & Mahapatra, 2012;Rahman 2019;Mohd Isa, Lim & Chin, 2019;Sadeh & Garkaz, 2019), benefits and risks of medical travel (Kumar et al, 2012), partnership quality between health institutions and travel agencies (Lin, 2014), and supply chain network modelling (Ahmadimanesh, Paydar & Asadi-Gangraj, 2019).…”
Section: Literature Reviewmentioning
confidence: 99%